PROSES MORFOLOGIS WAZAN-WAZAN FI’IL MAZID DAN MAKNANYA DALAM AL-QURAN JUZ 28 - Hakim, Muhammad Luqman (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2020)
This study is aimed to describe (1) wazan-wazan fi'il mazid which are in Al-Quran chapter 28, (2) morphological process in fi'il mazid in Al-Quran chapter 28, (3) morpho-phonemic process in fi'il mazid in Al-Quran chapter 28, (4) the meanings which are contained in fi'il mazid in Al-Quran chapter 28. This study is a descriptive qualitative study. The data source is Al-Quran chapter 28. Data that are taken is put in the analysis table, then being reduced corresponding to the aim of this study. The result of this study shows that: (1) It is found that there are 154 words in Al-Quran chapter 28 with wazan fi'il mazid, (2) Words with wazan fi'il mazid in Al-Quran chapter 28 is occurring two morphological processes on its formation, they are affixation process (affixes addition) and internal modification (harakat transformation). (3) Morphophonemic process of fi'il mazid in Al-Quran chapter 28 is occurring three kinds of process, they are (a) idgham, (b) i'lal, (c) ibdal, and (4) The alteration of meanings in every wazan has their own use/function.